Peran Guru dalam Membentuk Karakter Peserta Didik di Raudhatul Athfal (RA) Al-Barkah Panyabungan II Mandailing Natal - Sri Novita Yanti; Mukhlis; Zulpina (PT. Willy Print Art, 2025)
This study aims to explain the role of teachers in shaping the character of students at Raudhatul Athfal (RA) Al Barkah Panyabungan II, Mandailing Natal and to explain the supporting and inhibiting factors in shaping the character of students at Raudhatul Athfal (RA) Al Barkah Panyabungan II, Mandailing Natal. This type of research uses descriptive field research with a qualitative approach. The data collection methods are observation, interviews and documentation and are analyzed by reducing data, presenting data, and drawing conclusions. Based on the results of the research and studies conducted, the role of teachers in shaping the character of discipline of students at Raudhatul Athfal (RA) Al Barkah is to provide examples as role models, make habits, provide rewards and punishments, provide motivation and conduct evaluations and in the formation of children's disciplined character, researchers see several supporting and inhibiting factors. The supporting factors are the control of the principal, the existence of programs that support the development of children's discipline, cooperation between teachers and parents of children, and awareness of students. Then the inhibiting factors are the student's family and the playing environment.